PENGARUH STATUS SOSIAL SISWA PERBATASAN TERHADAP KOHESIVITAS SISWA SMP NEGERI 3 SAJINGAN SAMBAS - Nurul Azmisyah; Amrazi Zakso; Maria Ulfah (Jurnal Pendidikan dan Pembelajaran Khatulistiwa (JPPK), 2023)
This study aims to determine the influence of students' social status on the cohesiveness of students in SMP Negeri 3 Sajingan Sambas Regency. The method used in this study is descriptive method with quantifiative research form. The population in this study was 140 students with a sample of 104 students. Data collection used is through indirect communication (questionnaire) and documenter studies. In this study obtained 1) the average value of variable social status of students in SMP Negeri 3 Sajingan amounted to 34.62 classified in the low category, 2) the average value of cohesiveness of students in SMP N egeri 3 Sajingan amounted to 36.97 classified in the low category. 3) the fcalculate amounted to 10,756 which is greater than the ftabel value of 0.004 so that Ho was rejected and Ha accepted which means that the social status of students has an influence on the cohesiveness of students at SMP Negeri 3 Sajingan. The coefficient of determination (R2) indicates a number of 0.672 = 67.2 %. so that the percentage of the influence of student social status on student cohesion if 67.2%. So, there is an influence on the social status of junior high school students on the cohesiveness of students at SMP Negeri 3 Sajingan.